Transformasi Kompetensi Profesional Guru Pendidikan Agama Islam di Era Disrupsi Digital: Peran Ekosistem Kelembagaan terhadap Minat Belajar Siswa - Dedy Setiawan; Zamzami Zamzami (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to deeply analyze the role of Islamic Religious Education (PAI) teachers' professional competence in improving students' learning interest amidst digital disruption challenges, and to evaluate the impact of institutional ecosystem support on teacher professionalism. This study employs a qualitative approach with a case study design at UPTD SMP Negeri 1 Jatibarang. Data were collected through participant observation, in-depth interviews, and documentation studies, involving PAI teachers, the principal, and students. Data analysis was conducted using the Miles, Huberman, and Saldana model, encompassing data condensation, data display, and conclusion drawing, with validity tested through source and technique triangulation. The findings indicate that PAI teachers' professional competence is no longer limited to theoretical subject mastery but includes the contextualization of Islamic values, technology integration (TPACK), and personal approaches. Significantly, this study finds that teacher agency in creating engaging learning heavily relies on institutional ecosystem support, such as the optimization of MGMP (Subject Teacher Consultative Forums), principal academic supervision, and a collaborative school culture. Major obstacles include gadget distraction, student background heterogeneity, and time constraints. The novelty of this study lies in the assertion that improving student learning interest in the digital era cannot solely be burdened on individual teacher competence but demands a synergistic and supportive institutional ecosystem.